Around the world in twenty-one trumpets: a brass odyssey: an interdisciplinary approach to the fundamentals of brass playing using the natural trumpet - Hasselbring, Chris; Montgomery, Kirsty (Illinois Brass for Beginners LLC, 2017)
Those who have seen Chris Hasselbring and Kirsty Mongomerys presentations at various HBS events or other venues have seen one of the more innovative approaches to music pedagogy in recent times. Incorporating the use of natural trumpets incorporating an interdisciplinary approach to the study of history, they have created a fascinating approach to studying music. The most current incarnation of the book is comprised of 10 chapters divided into three units. The fictional hero of the book is Ragnar, a prehistoric trumpeter who takes the reader through musical and historical adventures. Sound files of musical examples, reference and review material and other resources are online at www.practicecave.com. The site Hear it online www.hearragnar.com additionally contains a narrative that reviews historical and musical elements of Ragnars tale.An Introduction outlines key historical and musical concepts and a timeline of lip-blown instruments. Unit one begins in prehistoric times and introduces basic musical ideas such as embouchure, breath control, and tonguing. Musical improvisation is introduced and it is paired with real-life prehistoric situations in which sounds could play a role. Unit Two proceeds historically with ancient Egyptian and Jewish use of wind-blown instruments. Exercises involving shofar calls and fanfares are given along with historical developments such as the invention of writing. Games and maps involving Oxus trumpets, and Celtic, Etruscan, Peruvian, Australian and Chinese instruments. Unit Three introduces ancient Greek and Roman musical instruments and history. Musical exercises are built on previous ideas discussed including the harmonic series, embouchure and articulation. Again improvised music for real-life situations are presented such as battle calls, dance music, and religious ceremony. Written notation is presented in this unit all of which are supported by the online web resources.Chris Hasselbring and Kirsty Montgomery have created an ingenious method for young brass students. While the book uses the study of history and the natural trumpet (in all its possible incarnations) this method could easily be the starting point for young students of any lip-vibrated instrument including horn, trombone or tuba. I would encourage music teachers working with young students to seriously consider this inventive approach.